Kualifikasi Pemuda Tani Perdesaan di Jawa Timur - Muksin Muksin; Margono Slamet; Djoko Susanto (Jurnal Penyuluhan, 2009)
This research objectives are: (1) to analyze characteristics and qualification of the farmer youth, (2) to explain the implication of famer youth qualification. The research population are all youth in East Java. The technique of data collecting was cluster sampling. The number of respondents are 251 of youth. The descriptive and correspondency data analysis was used to analyse the data. The research results were: (1) The degree of farmer youth education is low category (2) The qualification of farmer youth that have activity in agricultural sector is lower than rural youth that have activity in non agricultural sector, (3) Farmer youth need facilitation to grow and develop their competencies.